The influence of training and development on employee performance in the cleaning services of PT Nusantara Abadi Sejahtera Tangerang - Wibowo, Faathir Arthurio; Herayati, Herayati; Windasari, Vicky (Keynesia : International Journal of Economy and Business, 2025)
Low competence and job training in Indonesia cause employee performance to be less competitive. This research was conducted because of complaints related to the work ethic and discipline of PT Nusantara Abadi Sejahtera cleaning service employees who were considered lacking, thus reducing service quality. The study employed a quantitative approach, employing a saturated sample strategy for sampling. Data was collected from 56 employees through a combination of in-person interviews, questionnaires, and observational studies. The F and T tests were used for data analysis in order to see the partial and simultaneous effects of development and training on employee performance. A t-count of 3.344 and a significance of 0.002 indicate that training significantly affects employee performance, while a t-count of 2.053 and a significance of 0.045 indicate that development also positively affects performance. There is a statistically significant relationship between training and development and employee performance, as shown by the F-test results (F-count: 90.618, p = 0.000). It is clear that training and development programs have a substantial impact on employee performance, and this impact is both partial and simultaneous. As a result, it is crucial for firms to constantly enhance their training and development programs in order to boost employee performance.